Políticas culturais de lazer e esporte nas universidades públicas federais de Minas Gerais - Brisa de Assis Pereira (2018)
The present study, developed from the specific field of study of public policies, was aimed at debating the role of federal public universities of the state of Minas Gerais in formulating leisure and sport policies on campuses, through a documentary analysis of the Institutional Development Plans (IDP's) the Statutes and the General Regiments. From the analysis of the institutional philosophies, ideologies and principles governing the pedagogical practices of the public universities in Minas Gerais, I was able to verify that all of them define, in some greater or lesser extension, their responsibility with the promotion of an emancipatory, humanistic, integral and citizen education. In such a way, from the understanding of leisure and sport as constituents of citizenship and instruments of training and human emancipation, I sought to analyze the way those universities have looked at these dimensions. The results revealed that although all institutions contemplate leisure and sport in at least one of their documents, within the dynamics of most of them, it was developed by several organizational bodies (Student Assistance, University Extension, Physical Infrastructure) as isolated events and not as an effective animation policy (a process). Most universities have designed leisure and sport in a functional and welfare way, as a strategy for promoting health and quality of life; as a condition for the maintenance and permanence of the students in the institution; and as a possibility of contact and social interaction. Only four universities have indicated to understand them more broadly, as an integral part of the educational actions being developed and as a constitutional right that must be universalized. Not coincidentally were the most propositive in the development of leisure policies and indicated to have a specific organ for such purpose. The analysis of the Internal Regiments of the organs of these four universities highlighted their objectives, sources of funding, goals and actions, providing evidences to infer that the existence of specific organs for leisure and sport is a significant element in order to have concrete possibilities to implement these policies. Finally, I highlight the need for university structures to share the synergistically of a common goal, from a minimum consensus on the broadened conceptions of leisure, in order to develop a policy appropriate to its effect.